Single‐stage versus two‐stage arteriovenous loop microsurgical reconstruction: A meta‐analysis of the literature. Issue 6 (24th July 2017) - Knackstedt, Rebecca; Aliotta, Rachel; Gatherwright, James; Djohan, Risal; Gastman, Brian; Schwarz, Graham; Hendrickson, Mark; Gurunluoglu, Raffi
Abstract : Background: Arteriovenous (AV) loops can be utilized in a single‐ or two‐stage approach in free flap reconstruction when proper vessels are not available. However, there exists no consensus on which method leads to superior microsurgical and patient outcomes. The purpose of this article was to review single‐ versus two‐stage AV loops utilized in free flap reconstruction with a focus on complications and overall outcomes. Methods: A systematic review of AV loops for autologous free tissue transfer was conducted. Endpoints investigated included flap characteristics, timing to second stage, complications, and outcomes. A Student's t ‐test and forest plots were used for statistical analysis. Results: Thirty‐five unique papers discussed utilizing AV loops in a single‐ or two‐stage approach, yielding 260 and 98 single‐ and two‐stage AV loops, respectively. There was a statistically significant higher rate of major complications in two‐stage as compared to single‐stage AV loops. There was a non‐statistically significant difference in rate of minor complications in the single‐stage as compared to two‐stage AV loops. Overall, there was a statistically significant higher success rate in the single‐stage as compared to two‐stage AV loops Conclusion: There was a statistically significant higher rate of major complications and failures in two‐stage AV loops. As well‐conducted randomized controlled studies are nearly impossible to perform in this population, the decision to pursue a single‐ versus two‐stage reconstruction should ultimately be determined based on individual patient co‐morbidities, the size and etiology of defect, and the type of free tissue transfer planned.